Corticosteroids in Septic Shock Treatment: A Systematic Review of Efficacy and Side Effects - Mohammed Kanan (Asian Journal of Pharmaceutics (AJP), 2024)
Septic shock (SS) is a critical condition with high mortality rates ranging from 27 to 54% in intensive care units (ICU). This systematic review aimed to evaluate the effects of corticosteroids on SS treatment, with a focus on mortality rates, ICU stay duration, shock reversal, and potential side effects. A comprehensive literature search was conducted using PubMed, Scopus, and the Web of Science, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Six studies were selected for the systematic review, including meta-analyses of randomized controlled trials. The results showed that corticosteroids, particularly low-dose hydrocortisone, reduced 28-day mortality, ICU admissions, and hospital mortality. Corticosteroids also improved shock reversal, increased vasopressor-free days, and shortened the ICU stay. However, their use was associated with increased risks of hyperglycemia and hypernatremia. The optimal daily dose for mortality reduction was approximately 260 mg of hydrocortisone or its equivalent. While corticosteroids show promise in managing SS, their use remains controversial due to varied outcomes across studies. Personalized treatment, considering factors such as timing, dosage, and specific corticosteroids, is necessary to optimize the benefits and reduce risks. Further research is required to determine the optimal corticosteroid protocols and effectiveness of adjunct treatments.